Biomaterials science : an introduction to materials in medicine - Ratner, B. D. (Buddy D.), 1947- (Amsterdam ; Boston : Elsevier/Academic Press, 2013)
The revised edition of this renowned and bestselling title is the most comprehensive single text on all aspects of biomaterials science. It provides a balanced, insightful approach to both the learning of the science and technology of biomaterials and acts as the key reference for practitioners who are involved in the applications of materials in medicine.
Preface -- How to Use This Text -- Introduction -- Part 1. Materials Science and Engineering -- Section 1.1. Properties of Materials -- Section 1.2. Classes of Materials Used in Medicine -- Part 2. Biology and Medicine -- Section 2.1. Some Background Concepts -- Section 2.2. Host Reactions to Biomaterials and Their Evaluation -- Section 2.3. Biological Testing of Biomaterials -- Section 2.4. Degradation of Materials in the Biological Environment -- Section 2.5. Applications of Biomaterials -- Section 2.6. Applications of Biomaterials in Functional Tissue Engineering -- Part 3. Practical Aspects of Biomaterials -- Section 3.1. Implants, Devices, and Biomaterials: Special Considerations -- Section 3.2. Voluntary Standards, Regulatory Compliance and Non-Technical Issues -- Appendix A: Properties of Biological Fluids -- Appendix B: Properties of Soft Materials -- Appendix C: Chemical Compositions of Metals Used for Implants -- Appendix D: The Biomaterials Literature.
Includes bibliographical references and index.
Keywords: Biocompatible Materials; Biomedical materials